Association of quantitative sensory testing parameters with clinical outcome in patients with lumbar radiculopathy undergoing microdiscectomy. (14th June 2020) - Tampin, Brigitte; Slater, Helen; Jacques, Angela; Lind, Christopher R. P.
Abstract: Background/Aim: This study aimed to establish the somatosensory profile of patients with lumbar radiculopathy at pre‐and post‐microdiscectomy and to explore any association between pre‐surgical quantitative sensory test (QST) parameters and post‐surgical clinical outcomes. Methods: A standardized QST protocol was performed in 53 patients (mean age 38 ± 11 years, 26 females) with unilateral L5/S1 radiculopathy in the main pain area (MPA), affected dermatome and contralateral mirror sites and in age‐ and gender‐, and body site‐matched healthy controls. Repeat measures at 3 months included QST, the Oswestry Disability Index (ODI) and numerous other clinical measures; at 12 months, only clinical measures were repeated. A change <30% on the ODI was defined as 'no clinically meaningful improvement'. Results: Patients showed a significant loss of function in their symptomatic leg both in the dermatome (thermal, mechanical, vibration detection p < .002), and MPA (thermal, mechanical, vibration detection, mechanical pain threshold, mechanical pain sensitivity p < .041) and increased cold sensitivity in the MPA ( p < .001). Pre‐surgical altered QST parameters improved significantly post‐surgery in the dermatome ( p < .018) in the symptomatic leg and in the MPA ( p < .010), except for thermal detection thresholds and cold sensitivity. Clinical outcomes improved at 3 and 12 months ( p < .001). Seven patients demonstrated <30% change on the ODI at 12 months. Baseline loss of function in mechanical detection in the MPA was associated with <30% change on the ODI at 12 months (OR 2.63, 95% CI 1.09–6.37, p = .032). Conclusion: Microdiscectomy resulted in improvements in affected somatosensory parameters and clinical outcomes. Pre‐surgical mechanical detection thresholds may be predictive of clinical outcome. Significance: This study documented quantitative sensory testing (QST) profiles in patients with lumbar radiculopathy in their main pain area (MPA) and dermatome pre‐ and post‐microdiscectomy and explored associations between QST parameters and clinical outcome. Lumbar radiculopathy was associated with loss of function in modalities mediated by large and small sensory fibres. Microdiscectomy resulted in significant improvements in loss of function and clinical outcomes in 85% of our cohort. Pre‐surgical mechanical detection thresholds in the MPA may be predictive of clinical outcome.